A compatibility study between rice starch and some non-steroidal anti-inflammatories - Ferreira, Beatriz B. [UNESP]; da C. Holanda, Bruno B. [UNESP]; Lacerda, Luiz G.; Schnitzler, Egon; Vieira, Renata L.D.; Gaglieri, Caroline [UNESP]; Bannach, Gilbert [UNESP] (Elsevier, 2021)
The objective of this work was to mix three milled drugs – Ibuprofen, Naproxen, and Ketoprofen – with rice starch in different proportions and then evaluate its use as an excipient. Differential scanning calorimetry and X-ray powder diffraction verified that the starch was amorphized after the milling process. The samples exhibited similar thermal decomposition profiles, as observed by thermogravimetry. In addition, mid-infrared spectroscopy elucidated the milling process did not alter the functional groups of the starch or the drugs, even in the presence of ethanol. The morphology of the starch granules, as observed by the scanning electron microscope, confirmed decreased particles size and only a physical mixture for the systems. The presence of ethanol in the milling process did not influence the properties of starch or the active ingredients. Therefore, rice starch can be considered as an efficient excipient for these drugs.
Keywords: Excipient; Ibuprofen; Ketoprofen; Naproxen; Rice starch